A morphometric study of the middle and lower cervical vertebral endplates and their components. Issue 10 (March 2017) - Feng, Hang; Fang, Xiang-Yi; Huang, Da-Geng; Yu, Cheng-Cheng; Li, Hou-Kun; Zhao, Song-Chuan; Ge, Chao-Yuan; Bai, Ru-Hai; Hao, Ding-Jun
Abstract : Abstract: Cervical disc arthroplasty is a common method of treating cervical degenerative disease. However, the footprints of most prosthesis dimensions are obtained from data of Caucasian individuals. Besides, there is a large discrepancy between footprints of currently available cervical disc prostheses and anatomic dimensions of cervical endplates. We aimed to detail the three-dimensional (3D) anatomic morphology of the subaxial cervical vertebral endplate, utilizing high-precision, high-resolution scanning equipment, and provide a theoretical basis for designing appropriate disc prostheses for Chinese patients. A total of 138 cervical vertebral endplates were studied. Each endplate was digitized using a non-contact optical 3D range scanning system and then reconstructed to quantify diameters and surface area for the whole endplate and its components (central endplate and epiphyseal rim). The whole endplate and mid-plane concavity depth were measured. There is marked morphologic asymmetry, in that the cranial endplate is more concave than the corresponding caudal endplate, with endplate concavity depths of 2.04 and 0.69 mm, respectively. For the caudal endplates, the endplate concavity apex locations were always located in the posterior portion (81.42%), while in cranial endplates relatively even. The central endplate was approximately 60% of the area of the whole endplate and the anterior section of the ring was the widest. From C3/4 down to C6/7 discs, the vertebral endplate gradually became more elliptical. Chinese cervical endplate anatomic sizes are generally smaller than that of Caucasians. Although Korean and Chinese individuals both belong to the Asian population subgroup, the majority of anatomic dimensions differ. Singaporean cervical endplate morphology is very similar to that of Chinese patients. We performed a comprehensive and accurate quantitative description of the cervical endplate, which provide references to shape and profile an artificial cervical disc without sacrificing valuable bone stock. To design a device with footprint as large as possible to distribute the axial load, we suggest that additional attention should be paid to the marginal rim. It is essential to specifically design appropriate disc prosthesis for Chinese patients. To fit the morphologic and biomechanical variations, we also propose that the disc prostheses for different vertebral segments should be separately designed.